2018
DOI: 10.5056/jnm17145
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Practice Guidelines for Irritable Bowel Syndrome in Korea, 2017 Revised Edition

Abstract: In 2011, the Korean Society of Neurogastroenterology and Motility (KSNM) published clinical practice guidelines on the management of irritable bowel syndrome (IBS) based on a systematic review of the literature. The KSNM planned to update the clinical practice guidelines to support primary physicians, reduce the socioeconomic burden of IBS, and reflect advances in the pathophysiology and management of IBS. The present revised version of the guidelines is in continuity with the previous version and targets adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 143 publications
0
38
0
2
Order By: Relevance
“…10,11 However, the prevalence of IBS could differ depending on the clinical setting in terms of race, geography, community base, or whether a study was performed in a primary or tertiary hospital setting, as well as the enrolled number of men or women, definition criteria for IBS used (Rome vs Manning), or method of data collection (Postal questionnaire, telephone interview, self-administered questionnaire, or interview-administered questionnaire). [12][13][14][15][16][17][18] Moreover, differences in access to health care and cultural factors, such as help-seeking behavior, may contribute to prevalence differences as well. 6,13,[15][16][17][18] A recent systemic review for 83 studies conducted in 41 countries including 288 103 participants (55.0% women) by a Rome foundation working team showed significant variation in pooled regional prevalence; the mean prevalence among individual countries ranged from 1.1% in France and Iran to 35.5% in Mexico.…”
Section: Prevalencementioning
confidence: 99%
“…10,11 However, the prevalence of IBS could differ depending on the clinical setting in terms of race, geography, community base, or whether a study was performed in a primary or tertiary hospital setting, as well as the enrolled number of men or women, definition criteria for IBS used (Rome vs Manning), or method of data collection (Postal questionnaire, telephone interview, self-administered questionnaire, or interview-administered questionnaire). [12][13][14][15][16][17][18] Moreover, differences in access to health care and cultural factors, such as help-seeking behavior, may contribute to prevalence differences as well. 6,13,[15][16][17][18] A recent systemic review for 83 studies conducted in 41 countries including 288 103 participants (55.0% women) by a Rome foundation working team showed significant variation in pooled regional prevalence; the mean prevalence among individual countries ranged from 1.1% in France and Iran to 35.5% in Mexico.…”
Section: Prevalencementioning
confidence: 99%
“…The definition of agreement or other methods are the same as the previous guidance development method. 11 A total of 27 doctors participated in the first round of Delphi consensus. Specific methods, such as the criteria for consent, were the same as for the previous guidelines.…”
Section: Weak Againstmentioning
confidence: 99%
“…A recent guideline from Korea recommended that TCAs can be considered for symptom improvement in IBS patients. 11 Recently, 2 systematic reviews compared TCAs with placebo in patients with FD. 129,130 The first review included 4 RCTs and found that administration of TCAs was associated with reduced number of patients showing no improvement in symptoms compared with placebo (RR, 0.76; 95% CI, 0.62-0.94) with an NNT of 7 (95% CI, .…”
Section: Fundic Relaxantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, we found some papers (N = 15) that covered IBS therapeutic approaches where probiotics were recommended/evaluated as a highly recommended treatment option, but the authors of the different studies examined different IBS subtypes as mixtures or did not report on improved intestinal transit time/bowel movements frequency/stool consistency [75,87,90,[93][94][95][96][97][98][99][100][101][102][103][104]. These documents were not placed in Tables II-IV. Overall, there seemed to be an agreement that probiotics may improve intestinal motility, but medical authorities predominantly recommended probiotics as an integral part of treatment for constipation cautiously.…”
Section: Results Of Systematic Searchmentioning
confidence: 99%